Illusions of liberalism, influxes of imperialism and a socialist alternative - Ribeiro, Rodrigo Fernandes (Argumentum, 2022)
This article highlights elements hidden by liberalism to justify bourgeois sociability, and the limits that the free-market premise imposes on Latin American countries with dependent capitalism. Marxist analysis is used to explain: the genesis of capitalism and the primitive accumulation of capital; the colonization process and the current phase of imperialist domination; a bibliography that dispels illusions of liberal political and economic concepts. Finally, it discusses the Latin American model of capitalist development, showing that a socialist alternative is the only way to overcome dependence and backwardness, in a simultaneous movement of struggles within and against the order.